G235 What Did the Doctor Say? Measuring Information Decay in a Paediatric Assessment Unit. (4th June 2013) - Thewodros, S; Round, J
Abstract : Aims: As medicine becomes more complex, the need for effective communication increases. Changes in acute paediatrics have reduced opportunities for information transfer, with more Paediatric Assessment Units (PAU's) attendances and shorter inpatient stays. However parents still expect clinicians to explain the diagnosis and management. We therefore explored factors predicting effective information transfer to parents of children in a PAU. Methods: In a PAU serving 22, 000 patients/yr, doctor-parent interactions were observed after consent, noting the child's demographics, presentation variables and information covered. Parents were interviewed 2–4 hours later exploring what they remembered and how their perceptions of the earlier interaction. The study had been approved by the local ethics committee. Results: 20 patients, attending between 0900 and 1700 on weekdays were selected. Those not expected to stay after their consultation were excluded. Mean patient age was 7.75 yrs (range 10 months-15 years). 75% were boys. Mean number of items of information was 6.6 (range 4–10) per patient. Parents recalled a mean of 86% of these items (range 33–100%). There was no correlation between numbers of items covered and the number remembered, nor with demographics, interaction time, perceived anxiety or departmental noise. Those with better than mean recall more often had children who had suffered an injury rather than an illness, had overall lower illness severity (PEWS mean 0.91 vs 1.67; p = 0.08) and had shorter overall waiting times before being seen (2.5 vs 3.9 hours; p = 0.08) than those in the lower recall group. Conclusions: Despite the stressful PAU environment, we found good recall of given information in our sample group. Unexpectedly, better recall was unrelated to consultation time or items covered, but seemed better with traumatic presentations, when the child was less unwell and with shorter waits. Parents may more readily assimilate information in relation to more obvious or external conditions and when they are less stressed. These findings suggest extra consideration is placed upon information giving when the child is particularly unwell or has an illness rather than trauma.